ANODA SILIKON BERPORI DARI PROSES BALL MILL UNTUK BATERAI ION-LITIUM - Yosia Edward Koraag, Pierre
Lithium-ion battery is a secondary battery that is widely used on electronic gadgets and electric vehicles due to its high energy density compared to other secondary batteries. Lithium-ion batteries commonly use a graphite-based anode that has limited maximum specific capacity at 372 mAh/g. There are several ways to increase lithium-ion battery capacity, such as using silicon as the anode material, which has high specific capacity up to 4200 mAh/g. However, silicon has several drawbacks, such as low electrical conductivity, and massive volume expansion that can decrease the performance of the lithium-ion battery. Hence, strategies are developed to engineer the structure and composition of silicon to produce high-performance anodes. In this research, the silicon anode is synthesized by utilizing ball-milling and alkaline etching. As confirmed by SEM/TEM and BET surface area analysis, the as-produced silicon has an average size of 3 microns and a porous structure. From XRD data, there is a formation of amorphous silica on the porous silicon particle. Half-cell Li-ion batteries using porous silicon anode are assembled to determine the capacity and cycling stability of the ball-milled porous silicon anode. Despite the promising morphology, ball-milled porous silicon anode has a lower capacity than ball-milled silicon anode (without etching). This poor performance shows that creating a porous structure is not enough to increase the performance of silicon anode, and further processing is needed to improve its performance.